Judicial Control over the Practice of Polygamy: A Comparative Study of Religious Courts in Indonesia and Sharia Courts in Malaysia - Nashih Muhammad; Muhammad Nur Risqi; Ouedraogo Saidou (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2026)
This study examines Islamic family law in Indonesia and Malaysia, focusing on polygamy licensing practices at the Temanggung Religious Court and Sharia Courts in several Malaysian states. Although both countries legally permit polygamy subject to requirements of justice and capacity, they apply different legal frameworks. Indonesia adopts monogamy as the general principle, with strictly regulated exceptions under Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law, while Malaysia regulates polygamy through the Islamic Family Law (Federal Territories) Act 1984 and state Islamic family law enactments. Using a qualitative case study approach, this research combines document analysis with semi-structured interviews involving three key informants: a Temanggung Religious Court judge, a *fiqh munakahat* lecturer at UniSHAM Kedah, and a *maahad tahfiz* administrator in Selangor. Data were analyzed through reduction, presentation, and inductive conclusion drawing. The findings show that Indonesian regulations emphasize legally recognized grounds, the first wife’s consent, financial capacity, and the guarantee of equitable treatment. At the Temanggung Religious Court, approximately 60–70% of polygamy applications are rejected, mainly due to the absence of the first wife’s consent and insufficient financial capacity. In Malaysia, greater emphasis is placed on measurable financial capacity (approximately RM 4,000 per month per family), emotional fairness, transparency, compliance with Sharia Court procedures, and official registration. Although the first wife’s consent is strongly considered, it is not always an absolute requirement.